2010
DOI: 10.1645/ge-2416.1
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma Gondii in Pigs From Southern China

Abstract: The seroprevalence of toxoplasmosis in pigs was examined in China's southern Guangdong Province from March 2008 through May 2009. A total of 1,022 serum samples was collected from 12 administrative cities and assayed for Toxoplasma gondii antibodies by enzyme-linked immunosorbent assay test. The seroprevalence ranged from 0 to 58.1% and the average T. gondii antibody-positive prevalence was 27.0% (276/1,022), with breeding boars having the highest level at 39.6% (38/96) followed by breeding sows at 36.9% (52/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…This is likely due to the presence of large number of cats in public places and pig farms in Hunan province. T. gondii seroprevalence in sows in the present study was significantly higher than that in Yunnan (16.6%) [13] and Fujian provinces (14.4%) [14] but was lower than that in Guangdong province (36.9%) [12]. The differences in seroprevalence may be related to animal welfares, climates, and animal husbandry practices.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…This is likely due to the presence of large number of cats in public places and pig farms in Hunan province. T. gondii seroprevalence in sows in the present study was significantly higher than that in Yunnan (16.6%) [13] and Fujian provinces (14.4%) [14] but was lower than that in Guangdong province (36.9%) [12]. The differences in seroprevalence may be related to animal welfares, climates, and animal husbandry practices.…”
Section: Resultscontrasting
confidence: 49%
“…But unfortunately, the majority of those reports were published in local Chinese journals, which are not readily accessible to international readers. In spite of the high prevalence of T. gondii reported in pigs in China, limited information is available for T. gondii infections in sows [1214]. Moreover, a preliminary pilot survey showed that T. gondii may pose significant public health threats in this province [15].…”
Section: Introductionmentioning
confidence: 99%
“…Pork is one of the most popular meats in China. Seroprevalence of T. gondii in pigs is high in some Chinese provinces, for instance 16.9% in Yunan province [76], 27% in Guangdong province [77] and 53.4% in Zhejiang province [78], which are higher than that in USA (2.7%, [79]), Germany (4.1%, [80]) and Mexico (12.7%, [81]). There is still no meat inspection for T. gondii contamination in meat before it is sold for human consumption, nor any strict performance standards for processing meat and animal products, which gives a high risk of infection for these workers.…”
Section: Human Toxoplasmosis In Mainland Chinamentioning
confidence: 99%
“…Differences were considered statistically significant when p < 0.05. The overall T. gondii seroprevalence in Tibetan pigs in Nyingchi prefecture, Tibet, was lower than that reported in pigs in southern China's subtropical Hainan and Guangdong Provinces (Suo et al 2006;Zhou et al 2010). This is possibly related to different climate conditions in these areas.…”
Section: Discussionmentioning
confidence: 82%
“…Pig meat is an important foodstuff worldwide, and humans can acquire infections with T. gondii by ingesting undercooked pig meat containing tissue cysts. Surveys of seroprevalence of T. gondii infection in pigs have been reported throughout the world (Dubey 2009(Dubey , 2010Garcia-Bocanegra et al 2010;Holec-Gasior et al 2010), and there have also been surveys of T. gondii infection in pigs in several provinces of China in recent years (Suo et al 2006;Zou et al 2009;Huang et al 2010;Zhou et al 2010).…”
Section: Introductionmentioning
confidence: 99%